Transforming food systems towards sustainable healthy diets in Bangladesh, Ethiopia, and Viet Nam: A cross-country stakeholder analysis - Namugumya, Brenda Shenute; Fakhry, Hager; Herens, Marion; Huynh, Tuyen; Duong, Thanh Thi; Pham, Huong; Mengesha, Belay Terefe; Khatun, Wajiha (International Food Policy Research Institute, 2024)
The CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) recognizes the urgency of early stakeholder engagement to facilitate systemic changes towards sustainable healthy diets. This qualitative exploratory study aimed to provide insights about where stakeholders are active in food systems in Bangladesh, Ethiopia and Viet Nam and their characteristics. The conceptual framework of food systems for diets and nutrition proposed by the High Level Panel of Experts on food security and nutrition was used to map all stakeholders using a network analysis approach, in particular applying the degree centrality measure. This measure shows the food system domains with the largest number of stakeholder connections. The analysis reveals that centralization is spread across various food system domains. In Bangladesh, the areas with the most stakeholder connections are observed in the policy and governance and food environment domains. In Ethiopia, more connections were observed under the food environment, and production system domains and the outcomes related to diets, nutrition and health. In Viet Nam, it is the production system, storage and trade, packaging and processing, and food environment domains with the most stakeholder connections. Overall, platforms are active in policy and governance in all countries, suggesting that engaging with multi-stakeholder platforms is beneficial for SHiFT to advance the national agendas aimed at realizing sustainable healthy diets. Considering connectivity with food system domains, SHiFT can collaborate with all sectors. Moreover, focusing on stakeholders in the food environment, particularly on overseeing foodscapes for people, is essential. However, implementing food systems transformation requires identifying and engaging with other actors as well. However, there is limited representation of stakeholders in processing, transport, and retail, especially in Ethiopia and Bangladesh. International stakeholders emerge prominently from our analysis, suggesting that the food system narrative may still be primarily driven from an international/global perspective, resonating with the United Nations Food Systems Summit dialogues. To realize the ambitions of transitioning towards sustainable healthy diets for all, efforts must extend beyond projects/programs and engage national-level stakeholders.